Efficacy and safety of sorafenib in combination with gemcitabine in patients with advanced hepatocellular carcinoma: A multicenter, open‐label, single‐arm phase II study. Issue 3 (9th May 2014) - Srimuninnimit, Vichien; Sriuranpong, Virote; Suwanvecho, Suthida
Abstract Aims Currently, the only standard systemic treatment for advanced hepatocellular carcinoma is sorafenib monotherapy. The study was conducted to assess the efficacy and safety of the novel combination of sorafenib and gemcitabine in the treatment of advanced hepatocellular carcinoma. Methods Between March 2008 and October 2010, patients with advanced pathologically proven hepatocellular carcinoma who had not received previous systemic therapy and had Child–Pugh liver function class A or B received sorafenib plus gemcitabine. Treatment included 4‐week cycle of gemcitabine (1000 mg/m2 days 1, 8, 15) to the maximum of six cycles together with sorafenib (400 mg twice daily). Patient continued sorafenib until disease progression or withdrawal from other reasons. The primary end point is progression‐free survival. Results Forty‐five patients were enrolled in this study. The median progression‐free survival was 3.7 months (95% CI 3.5–3.8). The overall response rate was 4% with no complete responses and the disease control rate was 66%. The median overall survival (OS) was 11.6 months (95% CI 7.4–15.9). The median time to progression was 3.6 months (95% CI 3.4–3.7). The most frequently reported grade 3/4 treatment‐related adverse events included thrombocytopenia 33%, neutropenia 16% and hand‐foot skin reaction 13%. The study regimen was well tolerated. Conclusion The combination of sorafenib and gemcitabine in advanced hepatocellular carcinoma is generally well tolerated and has modest clinical efficacy. The median OS is up to 1 year. However, well‐designed randomized controlled trials with a sorafenib alone comparator arm are needed to confirm this finding.